Complete genome sequence of Xylanimonas cellulosilytica type strain (XIL07T). Issue 1 (January 2010) - Foster, Brian; Pukall, Rüdiger; Abt, Birte; Nolan, Matt; Glavina Del Rio, Tijana; Chen, Feng; Lucas, Susan; Tice, Hope; Pitluck, Sam; Cheng, Jan-Fang; Chertkov, Olga; Brettin, Thomas; et al.
Abstract Xylanimonas cellulosilytica Rivaset al. 2003 is the type species of the genusXylanimonas of the actinobacterial familyPromicromonosporaceae . The speciesX. cellulosilytica is of interest because of its ability to hydrolyze cellulose and xylan. Here we describe the features of this organism, together with the complete genome sequence, and annotation. This is the first complete genome sequence of a member of the large familyPromicromonosporaceae, and the 3, 831, 380 bp long genome (one chromosome plus an 88, 604 bp long plasmid) with its 3485 protein-coding and 61 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.